Os dois saques de Roma: romanos e bárbaros na Historiae adversus paganos de Orósio - Galante, Márcio Augusto (2019)
The purpose of this dissertation is to discuss, analyze and investigate the magnum opus of Hispanic historian and priest Orósio, entitled Historiae adversus paganos, written between 415 and 417 AD of a largely Christian character. However, such a work presents itself as a universal history focusing on the Roman Empire and Christianity. Therefore, the first part of this paper seeks to present the analysis of the work, proposing to investigate how the figure of the barbarian was formulated, relating two points of the history of Rome: the sacking in 387 BC (possibly in 390 BC) undertaken by Breno and the Gauls; and the loot of 410 AD starring Alaric and his Goths. More specifically, it intends to observe the Orosius's double glance at the cut-off episodes, first of all, the barbarian as the “Non-Roman” and their relation to the Roman world; second, the dichotomy between the Christian and the non-Christian as antagonistic elements of the society of the period. To do so, it is necessary evidence that Orósio, as a producer of a historical work, makes it possible through this access the past - to which the author and his written production belong - enabling the investigation of elements that made up the scenario of the Roman Empire of recent years from the fourth century and the beginning of the fifth century.